The social butterfly: hunted subjectivity and emergent masculinities among refugees. Issue 4 (2nd October 2019) - Ingvars, Árdís K.
ABSTRACT: In refugee worlds, young men's masculinities are moulded through experiences of safety and danger. This leads some to contest normative ideas of gender roles and create an alternative migrant masculinity that counters the hegemonic norm. This paper is based on ethnographic fieldwork carried out in Greece in 2012–2015 among leftist solidarity movements. Through analysing interviews and fieldnotes, I detected five elements influencing the development of alternative performances of masculinities; the men's own struggle for rights in their lands of origin; the men's experiences through their irregular journeys; marginalisation on multiple levels; an environment that encouraged safety for diverse identities; and lastly, leaders with transnational and local connections, who openly practice support for transgressing the boundaries of gender and sexual orientation. Through their assigned 'hunted' identity, the men would negotiate problems in external structures such as religion, politics, border controls, work and education. These problems were often internalised, but solutions were sought through respecting freedom of choice while simultaneously caring for fellow human beings. While the inclusive practices and discourses were not without ambiguities, the solidarity networks allowed cis heterosexual refugees the supportive space to visibly endorse the rights of other marginalised groups and to demonstrate their emergent masculinities.